Diferentes níveis de betaína sobre incidência de diarreia, desempenho, características de carcaça e parâmetros sanguíneos de suínos - Ribeiro, Paulo Roberto; Kronka, Rodolfo Nascimento [UNESP]; Thomaz, Maria Cristina [UNESP]; Hannas, Melissa Izabel; Tucci, Fernanda Marcussi; Scandolera, Antônio João; Budiño, Fábio Enrique Lemos (My University, 2011)
Thirty six piglets weaned at 19 days of age were useddistributed in a randomized block design, were used to evaluate the effects of the addition of crescent levels of betaine (0,0%, 0,1%, 0,2% e 0,3%) in the diets on the performance in initial, growing and finishing phases. The indexes of diarrhea incidence were monitored in the first 14 days post-weaning; and the blood parameters at 20, 75, and 150 days of age, as well as the carcass characteristics at the end of the experiment. It was not observed (P > 0,05) effect of the betaine on the diarrhea incidence. Significative differences (P < 0.05) were verified among treatments in the finishing phase for daily weight gain and feed conversion. Differences (P < 0.0001) among the days to the blood parameters analysed were also observed. In regard to the backfat thickness, it was verified significative difference (P < 0.05) among the treatments.
Different levels of betaine on diarrhea incidence, performance, carcass characteristics and blood parameters of pigs
Keywords: Backfat thickness; Feed conversion; Piglets; Weight gain; Suidae